Unlikely Friends of the Authoritarian and Atheist Ruler: Religious Groups and Collective Contention in Rural China. Issue 1 (20th January 2015) - Tao, Yu
Abstract: This article examines the roles played by rural religious groups in China's local contentious politics. More specifically, it aims to explore whether religious groups stimulate or reduce collective contention when the ruler is both authoritarian and atheist. Drawing on national survey data and comparative case studies, this article finds that collective contention is less likely to occur in villages with religious groups that simultaneously overlap with secular social organizations and local authorities, and are hence more likely to serve as credible communication channels between local states and discontented citizens. This finding highlights two important issues that are often side-lined, if not outright neglected, in the existing literature. First, the relationship between religious groups and collective contention is diverse rather than uniform. Second, this relationship is shaped not only by religious groups but also by other important players in the local political arena.